Bahasa Inggris - Hamdeni Medriosa; Jafril Tanjung; Maidiawati; Sabril Haris HG (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
The width of diagonal strut is not commonly known for having significant benefit to the lateral strength of brick walls. However, some researchers have resumed that strut width has a significant impact on lateral strength. Both experimental and analysis studies indicates that the width of the diagonal strut indeed has a significant impact on the lateral strength of brick walls. By employing the developed analytical model, it became evident that the width of the strut benefited the strength of the brick wall. The purpose of this research is to determine the effect of diagonal strut width on the lateral strength of brick walls. The methodology employed to ascertain the lateral strength of brick walls was by conducting a comparative analysis of the analytical and numerical outcomes from varied strut widths at the mid-span openings to the various form of openings. The analytical approach was conducted with the use of diagonal struts, while the numerical modeling was done with the Atena 2D software. The analytical results obtained were 65.15 kN for diagonal strut 1 and 73.75 kN for diagonal strut 2. The numerical results obtained were 64.7 kN for diagonal strut 1 and 75.7 kN for diagonal strut 2. The findings derived from this investigation substantiate the pivotal influence of strut width on the lateral strength of brick walls.